Correlation between the Duration of Ethambutol Therapy and the Toxic Optic Neuropathy Occurene in Patients with Multidrug-Ressistance Tuberculosis - Muhammad Hamdan1, Eko Wahono R.1, Kurnia Kusumastuti1, Laily Irfana1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Tuberculosis affects one-third of the world’s population. Increasing number of tuberculosis cases also leads to the increase of anti-tuberculosis drugs use, such as ethambutol. Ethambutol is one of the most effective and rarely resistant tuberculosis drugs. Objective: To determine the relationship between duration of ethambutol therapy with toxic optic neuropathy in tuberculosis patients Method: This study enrolled MDR-TB patients who visited MDR-TB Unit of Dr. Soetomo General Hospital from July 2014 until the sufficient amount of sample was achieved. The patients enrolled are those who met the inclusion and exclusion criteria. Inclusion criteria consisted of MDR TB patients treated with ethambutol therapy, aged of 20-69 years old, and whose VEP examination results showed extension of P100 latency. Results: The mean of <6 month duration was 3.24±1.348, while for the ?6 months was 11.71±5.764. This difference was statistically significant with p = 0.043. Conclusion: There is a correlation between duration of ethambutol therapy with toxic optic neuropathy in patients with MDR-TB.